Toxic chemical weapons of assassination and warfare: nerve agents VX and sarin - Chai, Peter R. (Toxicol Commun, 2017)
The use of VX and sarin as weapons of assassination and warfare raises important considerations for healthcare professionals who may encounter victims, bystanders, and responders who require prompt assessment and treatment. Chemical warfare agents such as VX and sarin constitute a considerable threat to the health of the civilian population, military personnel, and peacekeeping forces. Healthcare providers should recognize symptoms of nerve agent exposure, understand regional and international notification procedures for potential attacks, as well as the indications for and available supply of antidotal therapy.